PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DENGAN VISUAL MERCHANDISING SEBAGAI VARIABEL MODERATING - Maduretno Widowati; Agus Budi Purwanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
The background of this research is more and more consumers are turning to shop at the minimarket from the market tradisional. This indicates the tendency of consumers who see that the minimarket is more suitable to by needs. The Research aims to determine the effect of the service and location where Visual Merchandising as a variable can strengthen specific purchasing decisions konsumen. This study aims to provide a solution to increase the number of consumers amid increasingly fierce competition minimarket. The results showed that service quality has a positive and significant impact on purchasing decisions, location positive and significant influence on purchasing decisions, quality of service is getting stronger influence on purchase decisions when driven by the Visual Merchandising, Location stronger influence on purchase decisions when driven by the Visual merchandising.